2003
DOI: 10.1007/s00221-003-1747-3
|View full text |Cite
|
Sign up to set email alerts
|

CNS somatosensory-auditory interactions elicit or modulate tinnitus

Abstract: Evidence has accumulated linking clinical tinnitus to the somatosensory system. Most clinical tinnitus patients can change the psychoacoustic attributes of their tinnitus with forceful head and neck contractions. The significance of such somatic modulation of tinnitus was assessed by testing non-clinical subjects. Like clinical tinnitus patients, about 80% of non-clinical subjects who had ongoing tinnitus at the time of testing (whether or not they had been previously aware of it) could modulate their tinnitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(164 citation statements)
references
References 7 publications
5
145
0
8
Order By: Relevance
“…The identification of a somatic origin for her tinnitus thanks to the matching of self-reported history and modulation in the same somatic regions helped in addressing this patient to multidisciplinary somatic evaluation and treatment. Furthermore, the characteristics of tinnitus modulation found in this patient are consistent with what reported in the literature by some authors 32,33,41,42 . TMJ maneuvers induced an increase in tinnitus loudness, while NECK maneuvers induced a decrease of loudness.…”
Section: Comments On This Casesupporting
confidence: 92%
See 3 more Smart Citations
“…The identification of a somatic origin for her tinnitus thanks to the matching of self-reported history and modulation in the same somatic regions helped in addressing this patient to multidisciplinary somatic evaluation and treatment. Furthermore, the characteristics of tinnitus modulation found in this patient are consistent with what reported in the literature by some authors 32,33,41,42 . TMJ maneuvers induced an increase in tinnitus loudness, while NECK maneuvers induced a decrease of loudness.…”
Section: Comments On This Casesupporting
confidence: 92%
“…This case demonstrates that tinnitus modulation can be found even when no somatic disorder is present; in fact, somatic modulation of tinnitus is a widespread condition that can be present with or without underlying somatic disorders 31,40 . Furthermore, as previously discussed, several authors reported a large capability of somatic tinnitus modulation in multiple patient series ranging between 65.3% and 83.3% 32,35,[41][42][43]45,47,61,65 . In this patient, the negative history for self-reported somatic disorder suggests caution while taking into account a somatic origin for his tinnitus.…”
Section: Comments On This Casesupporting
confidence: 52%
See 2 more Smart Citations
“…[14,[17][18][19] Although the exact mechanism of tinnitus has not been discovered, it has been proposed that neural plasticity especially somatosensory inputs to the cochlear nucleus cause it. [20,21] On the other hand, the association of tinnitus and SB is not clear. Camparis et al [22] found that tinnitus frequency was higher in patients with SB and chronic facial pain.…”
Section: Discussionmentioning
confidence: 99%